The effect of play approach in throwing and catching learning towards self-regulated elementary school students - Iman Sulaiman Zamzami; Samsudin Samsudin; Shela Ginanjar; Iman Sulaiman Zamzami; Samsudin Samsudin; Shela Ginanjar (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2026)
The play approach is considered a learning strategy that aligns with the characteristics of elementary school students because it promotes active, exploratory, and meaningful physical activity. This approach has the potential to enhance students' self-regulation in the learning process. This study aims to determine the effect of using the play approach in physical education on students' self-management skills in throwing and catching in fifth grade at SDN 1 Kayuambon. The research method uses an experimental design with a randomized pretest-posttest control group. The study population included all 120 students in Class V at SDN 1 Kayuambon. Sixty students were randomly selected and divided into two groups: an experimental group of 30 students who received instruction using the Play approach and a control group of 30 students who received conventional instruction. Research instruments were used to measure student self-management aspects, and data were analyzed using paired and independent t-tests. The results showed a significant increase in self-management in the experimental group, with values of t = -10.027 and p = 0.000; the control group did not show a significant increase, with values of t = 0.858 and p = 0.398. The independent t-test results showed significant differences between the two groups (t = 3.359; p = 0.001), indicating that the play approach is more effective than conventional learning models in improving student self-management. In conclusion, the Play approach to physical education has a better influence on improving student self-management than conventional learning. Further research is suggested to apply the Play approach to other physical education materials, such as physical fitness, gymnastics, and swimming, and to investigate its impact on aspects of physical fitness, cooperation, and student discipline.